Insulin Inhibits Autophagy by Inhibiting the Binding of FoXO1 to the Promoter Region of GABARAPL1 - Hong, Tao; Wen, Jie; Mei, Lang; Li, Ruixiang; Zhou, Junlin; Li, Jiaoyang; Xiao, Xin-Hua (Hormone and Metabolic Research, 2023)
Hyperinsulinemia and insulin resistance in T2D have a potent suppressive effect on hepatic autophagy, however, the underlying mechanisms remain unclear. To explore the effect of insulin on hepatic autophagy and its possible signaling pathways, HL-7702 cells were treated with insulin with or without insulin signaling inhibitors. The interaction between insulin and the promoter region of GABARAPL1 was assessed through luciferase assay and EMSA. There were significant dose-dependent decreases in the number of intracellular autophagosomes and the protein levels of GABARAPL1 and beclin1 in insulin-treated HL-7702 cells. Insulin signaling inhibitors reversed the inhibitory effect of insulin on rapamycin-induced autophagy and autophagy-related gene upregulation. Insulin blocks the binding of FoxO1 to putative insulin response elements in GABARAPL1 gene promoter, leading to the repressed transcription of GABARAPL1 gene and the suppression of hepatic autophagy. Our study identified GABARAPL1 as a novel target of insulin in suppressing hepatic autophagy.
Keywords: autophagy; insulin, diabetes; forkhead box protein O1; gamma-aminobutyric acid A receptor-associated protein-like 1; hepatocellular carcinoma; type 2 diabetes